Effects of esterification, saturation and amount of fatty acids infused into the rumen or abomasum in lactating dairy cows. Issue 1 (4th February 2022) - Litherland, Noah B.; Beaulieu, Angela Denise; Reynolds, Christopher K.; Drackley, James K.
Abstract: Our objective was to determine the effects of chemical structure, amount, and site of infusion of long‐chain fatty acids (LCFA) in lactating dairy cows. Six multiparous Holstein cows were used in a 6 × 6 Latin square design with 21‐d periods. During d 1 to 14, 250 g/d of LCFA and during d 15 to 21, 500 g/d of LCFA were infused continuously into either the rumen or abomasum. Treatments were 1) Control (CONT); 200 g/d of meat solubles plus 12 g/d of Tween 80 in 10 L of water, administered half in the rumen and half in abomasum; 2) control plus mostly saturated LCFA into the abomasum (SFAA); 3) control plus mostly saturated LCFA into the rumen (SFAR); 4) control plus soy (mostly unsaturated LCFA) free fatty acids (FFA) into the abomasum (UFAA); 5) control plus soy triglycerides (TG) into the abomasum (TGA); and 6) control plus soy TG into the rumen (TGR). The first 10 d of each period were for adaptation and washout from the previous treatment. The diet consisted of 30% (dry matter basis) corn silage, 20% alfalfa silage and 50% concentrate. Cows infused with UFAA had lower dry matter intake and milk yield than those infused with SFAA or TGA and reductions were greater at the higher infusion amount. Milk fat yield was decreased by UFAA relative to other treatments. Unsaturated LCFA decreased milk fat yield more than saturated LCFA. All LCFA treatments decreased short‐ and medium‐chain FA in milk relative to CONT, with greatest decreases for UFAA. Apparent total tract digestibilities of nutrient fractions were decreased by UFAA compared with TGA and SFAA and tended to be lower at the higher infusion amount. Apparent digestibility of total fatty acids (FA) was greater for SFAR than for SFAA. Plasma glucagon‐like peptide‐1 was greater for cows infused with UFAA than SFAA or TGA and increased at the higher amount. Plasma cholecystokinin was greater for cows infused with LCFA compared with CONT. Postruminal unsaturated FFA reduced intake and digestibility of nutrients and FA compared with postruminal TG infusion; saturated FA did not decrease dry matter intake or disrupt nutrient digestion. Glucagon‐like peptide‐1 may be involved in regulation of feed intake by long‐chain fatty acids.